Morphology of Heschl's gyrus reflects enhanced activation in the auditory cortex of musicians - Schneider, Peter; Scherg, Michael; Dosch, Hans Günter; Specht, Hans Joachim; Gutschalk, Alexander; Rupp, André (Nature neuroscience, 2002)
Using magnetoencephalography (MEG), we compared the processing of sinusoidal tones in the auditory cortex of 12 non-musicians, 12 professional musicians and 13 amateur musicians. We found neurophysiological and anatomical differences between groups. In professional musicians as compared to non-musicians, the activity evoked in primary auditory cortex 19-30 ms after stimulus onset was 102% larger, and the gray matter volume of the anteromedial portion of Heschl's gyrus was 130% larger. Both quantities were highly correlated with musical aptitude, as measured by psychometric evaluation. These results indicate that both the morphology and neurophysiology of Heschl's gyrus have an essential impact on musical aptitude.